Gender differences in the pathways linking parental psychological control, emotion regulation, and psychological distress among university students with smartphone addiction - Xu, Liu; Arshat, Zarinah; Ismail, Nellie; Lulu, Shi (Routledge, 2025)
This research investigated gender disparities in parental psychological control and psychological distress among 1,276 Chinese undergraduates utilizing Partial Least Squares Structural Equation Modelling. Paternal psychological control had a positive correlation with reappraisal in males (t(male) = 3.420; P = 0.001 < 0.05), whereas no such correlation was observed in females (t(female) = 0.276; P = 0.783 > 0.05). Gender significantly mitigated this connection (Difference(male-female) = 0.298; P = 0.014 < 0.05). The mediating effect of reappraisal on the relationship between paternal psychological control and psychological distress was significant for males but not for females (Difference(male-female) = 0.297; P = 0.006 < 0.05). No significant gender differences were observed in maternal psychological control or inhibition (P > 0.05). The findings endorse gender-sensitive models and highlight the need for interventions targeting parenting practices and emotional regulation, such as parental guidance programs and cognitive-behavioral training to strengthen adaptive regulation strategies.